The Effects of Different Tasks in Multitasking on Idea Generation - Nelson, Rebecca; O'Driscoll, Sarah; Chinchanachokchai, Sydney (My University, 2017)
With the availability of mobile devices, consumers have a tendency to perform more than one task at a time. The purpose of this study is to examine different types of tasks in multitasking and how they affect consumers’ ability to generate ideas.
Color poster with text and bar graphs.
Keywords: Idea generation; Mobile phone use; Multitasking; Posters